Avaliação da Produção de Etanol a partir de distintos Híbridos de Milho na Região Oeste do Paraná - Eckert, Caroline Thaís (2016)
With the aim of find out what the best hybrid maize for ethanol production, according to characteristics of the state of Paraná Western region were evaluated 10 hybrids, and 9 have transgenic technology Bt and 1 conventional non-Bt . The experimental development, the field was conducted between February and October 2015, and used a randomized block with four replications, and the average test employee was Tukey test (≤0,05), along with Correlation Matrix (≤0,05) and Contrast Analysis (≤0,05). The laboratory tests were conducted productivity and yield of die (kg ha-1 and L ethanol ha-1), the starch content, of soluble solids, and the percentage of ethanol in the wort produced. The hybrids were in accordance with literature by the fact that the amount of biomass produced per hectare was relevant to the yield of ethanol liters per hectare, in the same way that the quality of the grains had been indispensable for the good performance of hybrids.